(untitled) (Research, Society and Development, 2025)
The present study aimed to evaluate the cardiopulmonary risks associated with electronic cigarette use in young people aged 15 to 24, through an integrative review of the literature. The research was conducted in databases such as SciELO, PubMed, Lilacs, and VHL (Virtual Health Library), using portuguese and english descriptors and the PICO strategy, with inclusion and exclusion criteria based on the PRISMA protocol. A total of 457 articles were initially identified, of which 17 met the established criteria. The results demonstrated that electronic cigarette use is associated with significant cardiovascular and pulmonary changes. Among the cardiovascular risks, the following stand out: elevated blood pressure, increased sympathetic activity, oxidative stress, inflammation, endothelial dysfunction, arterial stiffness, atherosclerosis, arrhythmias, angina, and acute myocardial infarction. Regarding pulmonary risks, a higher incidence of spontaneous pneumothorax, exacerbation of asthma and bronchitis, chronic obstructive pulmonary disease (COPD), and E-cigarette or Vaping product use-Associated Lung Injury (EVALI) were observed. It is concluded that electronic cigarettes represent a significant risk factor for the health of young people, potentially leading to chronic and life-threatening conditions. Thus, the intensification of preventive, educational, and regulatory measures is recommended, as well as the development of longitudinal studies that evaluate the long-term effects of using these devices.